Development of a Web-Based Party Equipment Rental Service (Case Study: Tarup Queen) - Nanda Maudy Afrilevi; yulina (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2026)
The management of party equipment rentals at Tarup Queen currently faces operational constraints due to the use of conventional systems, leading to ineffective stock availability information and the risk of scheduling errors (double booking). Furthermore, manual transaction and payment verification processes often slow down the administrative workflow. This research aims to develop a web-based party equipment rental service capable of providing real-time availability information and integrating an automated payment system. The development methodology employed is the Prototyping Method, which allows for active user involvement in evaluating the interface design and system flow before the final implementation stage. The primary features developed include an interactive product catalog, a booking calendar system, and payment gateway integration for automated transaction verification. The research results indicate that the implementation of this system can minimize human error in schedule recording, accelerate the reservation process, and enhance transaction transparency for customers. The implementation of this web-based service is expected to transform Tarup Queen’s operational governance to be more efficient and competitive.